Strategi Penguatan Sumber Daya Manusia Berbasis Community Based Tourism dalam Mendukung Kebangkitan Desa Wisata Tarabunga - Nurhafizhah Khairi; Alvienta Ardhana; Brigusti Oktavia Zalukhu; Clara Humaira; Eka Aisyah; Elyoenai Sitorus; Gian Ananta Hutagalung (Program Studi S1 Pariwisata, Universitas Muhammadiyah Gorontalo, 2026)
Community-based tourism (CBT)-based tourism village development has become an important strategy in promoting sustainable tourism development by strengthening the role of local communities as the main stakeholders. However, the implementation of CBT still faces several challenges, particularly related to limited human resource capacity and suboptimal destination management. This study aims to formulate CBT-based human resource strengthening strategies to support the development of Tarabunga Tourism Village and to identify the destination’s development stage using the Tourism Area Life Cycle (TALC) approach. This research employed a descriptive qualitative method using observation, in-depth interviews with nine informants, focus group discussions (FGDs) with fifteen people, and documentation techniques. Data were analyzed using the SOAR and TALC approaches. The findings reveal that Tarabunga Tourism Village possesses significant natural resource potential and opportunities for community-based economic development. However, the village still faces challenges, including limited human resource capacity, underdeveloped tourism attractions, and low levels of community participation. Based on the TALC analysis, Tarabunga Tourism Village is currently at the involvement stage. Therefore, strengthening human resources based on CBT is considered the main strategy for supporting sustainable tourism village development through community capacity building and strengthened stakeholder collaboration.